MENINGKATKAN KEMAMPUAN KINESTETIK ANAK MELALUI PEMBELAJARAN TARI KREASI BINATANG LAUT - Sri Rahayu; Badru Zaman; I Gusti Komang Aryaprasetya (Prodi PGPAUD, 2019)
Abstrac : Improving Children’s Kinesthetic Skills Through The Teaching And Learning Of Ocean Animal Creative Dances. The background to the research is the problem found in Taman Kanak-Kanak (Kindergarten, shortened into Indonesian TK) Kebon Baru Utara, Kesambi District, Cirebon City, namely a lack of instruction that can stimulate kinesthetic skills, causing children’s kinesthetic skills to be low. In general, the research aims to find about efforts of improving the kinesthetic skills of Class B students of TK Kebon Baru Utara through the teaching and learning of ocean animal creative dances. More specifically, it aims to find about the objective conditions of group B children’s kinesthetic skills at TK Kebon Baru Utara, the implementation of the teaching and learning of ocean animal creative dances to group B children at TK Kebon Baru Utara, and improvement in children’s kinesthetic skills after the implementation of ocean animal creative dances to group B TK Kebon Baru Utara.The research employed Classroom Action Research method collaborating with the homeroom teacher. The subjects consisted of 12 class B children of TK Kebon Baru Utara, Kesambi District, Cirebon City, with 3 and 9 female and male students, respectively. Based on the findings, it is found that through the implementation of ocean animal creative dances teaching and learning to class B of TK Kebon Baru Utara, Kesambi District, Cirebon City, children’s kinesthetic skills improved in each of the cycles. The improvement in children’s kinesthetic skills was observed since the pre-cycle, in which it developed very well for 7%, then rose to 27% in cycle I, and increased to 75% in cycle II. Hence, it can be concluded that through the teaching and learning of ocean animal creative dances, children’s kinesthetic skills increased from cycle I to cycle II for 48%. This improvement was observed in children’s ability to coordinate their head, body, hands, and legs according to the rhythm and in their demonstration of agility in dancing. Thus, the researcher recommends teachers to implement the teaching and learning of ocean animal creative dances that are more varied in order to maximally increase and develop children’s kinesthetic skills.Abstrak : Meningkatkan Kemampuan Kinestetik Anak Melalui Pembelajaran Tari Kreasi Binatang Laut. Penelitian ini dilatarbelakangi oleh adanya permasalahan yang ditemukan di Taman Kanak-kanak Kebon Baru Utara Kecamatan Kesambi Kota Cirebon yaitu masihrendahnyakemampuan kinestetik anak.Oleh karena itu, penelitian ini bertujuan untuk mengetahui kondisi objektif, penerapan pembelajaran tari kreasi binatang laut, serta peningkatan kemampuan kinestetik pada anak kelompok B di TK Kebon Baru Utara melalui pembelajaran tari kreasi binatang laut. Metode yang digunakan adalah penelitian tindakan kelas (PTK) yang berkolaborasi dengan guru kelas. Subjek penelitian ini anak-anak kelompok B TK Kebon Baru Utara Kecamatan Kesambi Kota Cirebon yang berjumlah 12 orang. Berdasarkan hasil penelitian yang dilakukan kemampuan kinestetik anak menunjukan adanya peningkatan kemampuan kinestetik anak dari setiap siklusnya terlihat dari pra siklus tidak ada anak yang berada pada kategori BSH, pada akhir siklus I mengalami sedikit peningkatanakhir siklus II tidak ada anak yang berada di kategori BB. Maka dapat disimpulkan kemampuan kinestetik anak kelompok B TK Kebon Baru Utara melalui pembelajaran tari kreasi binatang laut mengalami peningkatan dari akhir siklus I ke akhir siklus II. Oleh karena itu peneliti merekomendasikan kepada guru untuk memberikan pembelajaran tari kreasi binatang laut yang lebih beragam lagi agar kemampuan kinestetik anak dapat berkembang dan meningkat dengan maksimal.